Mychailin I. L. Realism of the postmodernism period in Mychailo Olefirenko’s creative works - Mychailin I. L. (Philological Treatises, 2020)
The article presents analysis of novels “Whirlpool” and “Farmers” from seven-volume country epopee “Time of sloe flowering” by M. Olephirenko to comprehend his realism principles. His intense to describe Ukrainian reality as an inner integrity, to present country life by colorful heroes with their behaviour models and linguistic practice is emphasized. The researcher considers that M. Olephirenko befittingly continues the traditions of classical prose of I. Nechui-Levitsky, Panas Myrnyi and M. Kotsubinskyi in Ukrainian village describing.